Codifier le divorce international : Quelques remarques sur le projet GEDIP - Etienne Pataut (Acta Universitatis Carolinae. Iuridica, 2020)
The EU legislator has modified once again the so-called Brussels 2 bis Regulation. The new regulation 2019/1111 adds new provisions on parental responsibility and child abduction, but leaves those on divorce largely untouched. To the contrary, the GEDIP, an expert group of academics in private international law from across Europe, has established an indepth proposal for a new regulation on divorce. This paper analyzes the proposal which seeks to modernize and improve the current situation that has been widely criticized. The proposed regulation covers choice of law, jurisdiction and recognition. It allows limited party autonomy, both in jurisdiction and choice of law, and suggests significant improvements of the provisions on objective jurisdiction. It also recommends a recognition mechanism that would apply to judgements from third States and provides for a comprehensive set of rules concerning private divorces.